The Effect of Interactive-Read Aloud Strategy on the Extroverted and Introverted Students' Reading Comprehension - Apandi, Apandi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
This research investigated the most effective strategy of interactive reading aloud on the students' personality types in reading comprehension. In this research, the researcher employed quantitative research by using factorial design. Population in this research were the forth semester students of English intensive program in middle level and the sample were 40 students from experimental and control classes. Try out was conducted to measure validity and reliability of instrument. Two ways ANOVA was conducted to test the hypotheses, two-way analysis of variance with F-test at the 5% (0.05) level of significance.The probability based on the personality was 0.043< 2.024, meaning that there was difference between personality types and the use of strategy. The probability based on strategy was 0.374< 2.024, meaning that there was difference result between extroverted and introverted learners. And the probability based on interaction was 0.001< 2.024, meaning that there was interaction between strategy and personality types. In conclusion, there was interaction among interactive reading aloud strategy, students' personality types and reading comprehension. The used of interactive reading aloud significantly influenced to the extroverted students rather than introverted students.